Security and risk management in outdoor sports – an exploratory systematic review - Mata, C.; Carvalhinho, L. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The development and growth of tourism has increased the practice of nature and adventure sports, which is directly correlated to the risk inherent to the unpredictability of the environment and human reliance. In this exploratory systematic review, we set out to search for insight attained in the last decade, regarding safety and risk management in outdoor sports. We use the following sources: electronic databases (web of knowledge, b-on, rcaap), plus master’s and doctoral dissertations. The keywords used in our research were, in Portuguese, English and French: “Risk”; “Safety and risk management sport”; “Safety and risk management in adventure sports”; “Risk in outdoor activities”; “Risk in adventure sports”; “Safety in adventure activities”. From the 40 articles selected, only 33 attended to the necessary criteria: empirical studies of the past 10 years, pertaining academic dissertations, scientific articles or books. It resulted in 33 selected readings, comprising 17 international studies and 16 national.